Estudo de adsorção de corantes por diferentes nanoaluminas utilizando espectroscopia de absorção no visível - Victor Brendo Caldeira Fagundes (2024)
In this work, alumina nanoparticles were used to study the adsorption of dyes in aqueous solution, using visible spectrophotometry, in order to study the ability to remove contaminants from water. The work consisted of using two types of alumina in the gamma phase, γ-Al2O3, one of commercial origin (n-NAC) and the other produced by the laboratory, (n-LMN) to study the adsorptive capacity of the materials in the presence of dyes (Orange G and Indigo Carmim), using batch adsorption methodology. The nanoalumina produced by the laboratory was characterized using X-ray diffraction, transmission electron microscopy and gas adsorption, verifying its phase. The influence of pH on the adsorption processes and contact time for both nanomaterials was investigated, verifying that anionic dyes were preferred over cationic ones. Finally, the adsorption isotherms were analyzed and compared with mathematical models. For n-LMN nanoalumina, an adsorption capacity of 137.7 mg g-1 was observed, using the Langmuir model, for Alaranjado G, a result compatible with the literature and with commercial nanoalumina. The n-LMN nanoalumina showed good adsorption capacity for Indigo Carmine pilot tests. Both nanomaterials did not prove to be good adsorbents against cationic dyes, such as Methylene Blue, Malachite Green and Rhodamine B, due to the surface differences of both nanoalumina.